Iowa Birdline update, October 26, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for October 26, 1992. Highlights of the update include sightings of a female Vermilion Flycatcher a bird that has been seen only twice before in the state, a Black-bellied Plover, Sanderling and Dunlin. Also included are handwritten notes for the next week's update with sightings of a Cattle Egret and three female Surf Scoters. Epson - sheet feed/flatbed